Self-reported concussion history among midwestern skiers and snowboarders - Marko Ivancich; Vince Berry; Michael Clark; Andrew Beaumont; Corina Norrbom; Jeffrey C Amundson (Concussion)
Aim: To assess the rate of self-reported concussion in midwestern skiers and snowboarders. Patients: Recreational skiers and snowboarders between the ages of 14 and 69 years during a single winter ski season (2020–2021) at a ski area in Wisconsin, USA. Methods: Survey study. Results: Among this survey population (n = 161), 9.32 and 19.25% reported one or more diagnosed concussion and suspected concussion respectively as a result of a skiing- or snowboarding-related incident. Skiers and snowboarders that self-identified as advanced, those who utilized terrain park features, and those that participated in freestyle competition had significantly higher self-reported rates of concussion. Conclusion: Self-reported concussion history indicates a concussion prevalence that is higher than expected based on previous studies. Participants reported significantly more suspected concussions than diagnosed concussions, indicating a possible issue with underreporting in this population.